Tepubina Bandar: Isu dan Kaitannya Dengan Kesihatan Ekosistem Lembangan Saliran - Noorazuan, M. H.; Asmala, A. (Universiti Kebangsaan Malaysia, 2007)
Research related to urban imperviousness impact became an important agenda in catchment hydrological studies, both in developed and developing countries. The main objective of this study is to understand the equilibrium of environment-development linkages – specifically to study the effects of urban imperviousness on ecosystem health. Urban imperviousness as a river ecosystem health indicator has become widely accepted by river catchment professionals, especially in the United States of America and also elsewhere. Catchment imperviousness is not solely applied in environmental planning and river ecology, but has also recently been used to formulate new urban planning strategies to enhance environmental quality. In the context of catchment hydrology, imperviousness prevent infiltration and seepage to occurred, thus affecting the streamflow characteristics and basin’s hydrological cycle. This article highlights global and local issues related to imperviousness, its research methodological development and its potential use as an ecosystem health indicator for catchment areas in Malaysia.